Agile: it's time to put it to use to manage business complexity. Issue 5 (21st September 2015) - Denning, Stephen
Abstract : Purpose: – Once executives understand how Agile and Scrum can manage the extraordinary complexities of software development, they will realize they can use the same management expertise to manage the mounting complexity of the rest of their business. Design/methodology/approach: – The author explains that although the ideology of Agile puts emphasis on collaboration and teams, particularly self-organizing teams, managers should not confuse Agile teams with the generally unsuccessful efforts throughout the 20th Century to make teams a central and permanent aspect of management. Findings: – In effect, Agile and Scrum represent a major management discovery, a scalable system to produce continuous customer-focused innovation in a dynamic business environment. Practical implications: – Agile and Scrum can deal directly with current business issues by giving an authoritative voice to the customer and giving business and technical competence a preeminent role over authority. Originality/value: – Agile/Scrum is enjoying added attention from managers in collaborative work arrangements such as networks and ecosystems. These arrangements can be scaled without sclerosis and seemingly without limit.